Case report: Paradoxical manifestation of covid 19 induced thyroiditis in the unvaccinated patient. (August 2022) - Poudel Jaishi, Prakash; Neupane, Sandhya Kiran; Neupane, Prabhat Kiran; Koirala, Divya; Kandel, Arjun; Joshi, Kushum
Abstract: Introduction and importance: Subacute thyroiditis (SAT) is a self-limiting viral or post-viral thyroid illness with triphasic clinical history of thyrotoxicosis, hypothyroidism and restoration to normal thyroid function. COVID-19 have wide range of clinical manifestation involving both respiratory and non-respiratory symptoms. Subacute Thyroiditis is one of the emerging symptoms of COVID-19 infection. We reviewed various articles from different online platforms and found that viral antigen binds to HLA B35 molecules on the macrophages which activates cytotoxic T lymphocytes which damage the thyroid follicular cells by binding to ACE2 receptors. Case: We presented a case of COVID-19 induced subacute thyroiditis in an unvaccinated male patient whose physical symptoms manifested in the second week of infection. He presented with History of difficulty breathing associated with increased perspiration, generalized body weakness. Clinical findings and investigation: His clinical Findings and laboratory finding were suggestive of subacute thyroiditis. Intervention and outcome: The patient had been followed for a period of 15 days and was treated effectively with steroids which improved his symptoms. He was also counseled for vaccination. Highlights: Subacute thyroiditis has triphasic clinical history of thyrotoxicosis, hypothyroidism and restoration to normal thyroid function. Covid 19 has pulmonary and extrapulmonary manifestation. Subacute thyroidits is one of the rare manifestation of the Covid 19. Sub Acute thyroiditis can be treated with steroid which resolves the symptoms. Workup for thyroidits must be done for patient with covid 19 infection and symptoms of Thyroid Disorder.